SERBIAN TRANSLATION OF FRENCH CODE OF CIVIL PROCEDURE (1806) FROM 1837 - Stanković, Uroš (Zbornik radova Pravnog fakulteta u Novom Sadu, 2015)
The article deals with Serbian translation of French Code of Civil Procedure (1806), drafted in 1837 by Serbian politician and writer Lazar Zuban. He translated the Code not from his original text, but from one or several German translations. Zuban commenced its work on January 11th, 1837. However, one do not know when the translation was completed.        Serbian translation does not fully correspond with the original Code. The translator omitted, amended or supplemented the Code’s provisions unsuitable for the circumstances in his country. Omittances were either complete or partial, based on whether some matter was omitted wholly or partly. Amendments could be divided into necessary, adapting and explicative. By necessary amendments are understood all alterations of the original text dealing with the provisions impossible to remain in a code written for a country other the France. Adapting amendments changed French text in a manner to become applicable in Serbia. By using explicative amendments the translator broadened original text in orther to bring about its better understanding within people in his country. Zuban inserted full and partial supplements of the Code in his translation. Full supplement meant inserting a whole new article, whereas partial supplement signified putting additional text in already existing provisions of a Code. All omittances, amendments and supplements were appropriate, so one could tell that Zuban made a good amalgam of the original Code and then Serbian law.